Detecting and quantifying ongoing decay of organic archaeological remains: A discussion of different approaches. (14th May 2015) - Matthiesen, Henning
Abstract: In situ preservation is increasingly a preferred option for managing archaeological remains, as there is a wish to preserve some undisturbed remains for later generations to investigate using new methods and asking new questions. However, in situ preservation is only a viable option if the remains are well protected and are not undergoing rapid decay, and it requires a detailed knowledge of decay processes and rates. For instance it is well established that the presence of water is of paramount importance for the preservation of organic material, and there are several examples where archaeological remains in wetlands have been preserved under waterlogged conditions for thousands of years, only to be degraded within a few years or decades after drainage of the wetland. What is less clear is the importance of the water quality, and exactly how much water is necessary to prevent or minimize decay. Thus, for the management of archaeological sites it is necessary to develop tools and methods that allow us to discover ongoing decay as fast as possible. Furthermore, in order to prioritize between excavation, in situ preservation and mitigation the decay rate should be evaluated on a quantitative scale to determine if the archaeological remains can be preserved for centuries, decades or only a few years under different conditions. This is a challenging task as archaeological sites and materials are often heterogeneous and have been subjected to different site formation processes. This paper describes different approaches that may be used for determining decay rates of archaeological remains, and discusses their advantages and disadvantages. It is argued that it is necessary to combine several approaches to estimate decay rates and reach a reliable understanding of the decay.